1999
DOI: 10.1046/j.1365-2249.1999.00772.x
|View full text |Cite
|
Sign up to set email alerts
|

Patients with systemic lupus erythematosus (SLE) have a circulating inducer of interferon-alpha (IFN-α) production acting on leucocytes resembling immature dendritic cells

Abstract: Patients with active SLE often have an ongoing production of IFN-alpha. We therefore searched for an endogenous IFN-alpha-inducing factor (IIF) in SLE patients and found that their sera frequently induced production of IFN-alpha in cultures of peripheral blood mononuclear cells (PBMC) from healthy blood donors, especially when the PBMC were costimulated with the cytokines IFN-alpha2b and granulocyte-macrophage colony-stimulating factor (GM-CSF). The phenotype of the IFN-alpha-producing cells (IPC) as determine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

9
185
2

Year Published

2001
2001
2006
2006

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 222 publications
(196 citation statements)
references
References 34 publications
9
185
2
Order By: Relevance
“…We have previously shown that both SLE IIF and the combination of apoptotic cells and SLE IgG induced IFN␣ production exclusively in the NIPC/PDC population (23,32). We extended these observations in the present study by demonstrating that NIPC/PDCs, enriched on the basis of BDCA-4 expression, produced high levels of IFN␣ in response to material from both apoptotic and necrotic cells, combined with SLE IgG.…”
Section: Discussionsupporting
confidence: 85%
See 4 more Smart Citations
“…We have previously shown that both SLE IIF and the combination of apoptotic cells and SLE IgG induced IFN␣ production exclusively in the NIPC/PDC population (23,32). We extended these observations in the present study by demonstrating that NIPC/PDCs, enriched on the basis of BDCA-4 expression, produced high levels of IFN␣ in response to material from both apoptotic and necrotic cells, combined with SLE IgG.…”
Section: Discussionsupporting
confidence: 85%
“…We previously found that the IICs demonstrated in blood contained DNA and not RNA (23), but the present study demonstrates that apoptotic and necrotic cells in vitro also released RNA that was a potent IFN␣ inducer when combined with SLE IgG. One explanation for this apparent discrepancy is that while the RNA released from dying cells in tissues in vivo may be an important IFN␣ inducer at the tissue level, it is then degraded by RNases and therefore not readily detected in the circulation.…”
Section: Discussioncontrasting
confidence: 67%
See 3 more Smart Citations